2015
DOI: 10.1158/0008-5472.can-14-1540
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Invasive Brain Tumors Using a Chain-like Nanoparticle

Abstract: Glioblastoma multiforme is generally recalcitrant to current surgical and local radiotherapeutic approaches. Moreover, systemic chemotherapeutic approaches are impeded by the blood-tumor barrier. To circumvent limitations in the latter area, we developed a multicomponent, chain-like nanoparticle that can penetrate brain tumors, composed of three iron oxide nanospheres and one drug-loaded liposome linked chemically into a linear chain-like assembly. Unlike traditional small molecule drugs or spherical nanothera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 46 publications
2
81
0
Order By: Relevance
“…228,243 Other alternative strategies were found in this search. Researchers developed stimuli-responsive liposomes that were able to release DOX in a controlled manner in response to an external low-power radio frequency field 209 or local temperature rise. 218 Both strategies showed an improvement of DOX delivery across the BBB and prolonged survival time of animals.…”
Section: Design Of Liposomal Drug-delivery Systems For Glioma Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…228,243 Other alternative strategies were found in this search. Researchers developed stimuli-responsive liposomes that were able to release DOX in a controlled manner in response to an external low-power radio frequency field 209 or local temperature rise. 218 Both strategies showed an improvement of DOX delivery across the BBB and prolonged survival time of animals.…”
Section: Design Of Liposomal Drug-delivery Systems For Glioma Therapymentioning
confidence: 99%
“…It was also demonstrated that just angiopep-2 peptide was able to target BBB and glioma cells at the same time, 219 and RGD peptide targeted both BBTB and tumor cells. 204,207,209 PDT uses photosensitizing agents, such as Photofrin, for brain tumors, along with light of appropriated wavelength to kill glioma cells. The PDT cell-killing mechanism is directly related to the production of reactive oxygen species, which leads to cell apoptosis, with minimal side effects.…”
mentioning
confidence: 99%
“…In vivo, the vascular targeting NPs with a rod shape displayed a higher accumulation in the lung and brain than that of spherical NPs. Peiris et al established chain-like NPs, which showed much higher brain tumor accumulation (Peiris et al 2015). Compared with traditional chemotherapy, the chainlike NPs delivered 18.6-fold greater drug to the brain tumor, resulting in considerably better anti-tumor effect.…”
Section: Particle Size and Shapementioning
confidence: 99%
“…However, despite recent advances in targeted immunotherapeutics using biomaterials, 22,23,25,27 there is limited understanding of how carrier design simultaneously affects retention and accumulation in both the skin injection site and its dLN. Previous studies have explored the effects of biomaterial carrier size, 21,28 charge, 29,30 hydrophobicity, 31,32 and shape 33,34 on various aspects of transport, cellular uptake, and adaptive immune response.…”
Section: Introductionmentioning
confidence: 99%